Sport entrepreneurship and innovation - Ratten, Vanessa; Ferreira, João J. M. (Routledge, Taylor & Francis Group, 2017)
Featuring international authors discussing the role of entrepreneurship and innovation in the sports context, this work focuses on topics such as the role of entrepreneurial marketing in sport, how technological innovation has changed the way sport is played and viewed, the globalisation of sport as a product and service, the new types of sports that have emerged, athlete entrepreneurs and their related business endeavours and how sport influences innovation in other industries.